2019
DOI: 10.32526/ennrj.17.4.2019.30
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Land Use and Land Cover Change on Ecosystem Service Values: A Case Study of Khon Kaen City, Thailand

Abstract: Land use and land cover change (LULCC) by unplanned and uncontrolled urban expansion have a significant effect on ecosystem service values (ESVs). Objectives of the study were (1) to extract LULC status and its change between 2006 and 2016; (2) to predict two different LULC scenarios in 2026 and; (3) to assess LULCC impact on ESVs. Herein, Landsat imageries in 2006, 2011 and 2016 were used to classify LULC types by object-based image analysis (OBIA) and the derived results were applied to predict LULC in 2026 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Therefore, we assigned waterbodies as 'wetlands' instead of lakes/rivers. Although the LULC categories and equivalent biomes do not perfectly match, their use proved feasible in many other studies [17,[66][67][68]. LULC types, equivalent biome, and corresponding value coefficient are presented in Table 3.…”
Section: Assignment Of Ecosystem Services Values (Esv)mentioning
confidence: 99%
“…Therefore, we assigned waterbodies as 'wetlands' instead of lakes/rivers. Although the LULC categories and equivalent biomes do not perfectly match, their use proved feasible in many other studies [17,[66][67][68]. LULC types, equivalent biome, and corresponding value coefficient are presented in Table 3.…”
Section: Assignment Of Ecosystem Services Values (Esv)mentioning
confidence: 99%
“…The ESV for Chonburi is twice that of Shenzhen (865.66 million USD in 2006 and 877.03 million USD in 2016). The ESV of Chonburi was compared with that of Khon Kaen relying on the work of Ongsomwang et al [35]. The estimated total ESV of Khon Kaen in 2006 was 145 million USD, and projected to decrease to 132 million USD in 2026.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the built-up area increased while the water bodies decreased and the ESV of Anhui province decreased from 30,015.58×10 7 CNY in 2000 to 29,683.74×10 7 CNY in 2015. The relevant research in Thailand includes the work of Ongsomwang et al [35], who assessed the impact of land use changes on the ESV of Khon Kaen Province, Northeastern Thailand. These researchers found that agricultural land use decreased while rangeland, urban, and built-up areas dramatically increased.…”
Section: Applied Environmental Researchmentioning
confidence: 99%
“…Besides, visual interpretation of image features, e.g., shape, size, color, and texture for each class of LULC, was also performed to correct the misclassified LULC types (Mamat et al, 2018a;Ongsomwang et al, 2019;Thakkar et al, 2017).…”
Section: Lulc Classificationmentioning
confidence: 99%
“…Where; ESV is the total estimated ESV, positive values of ESV indicate an increase, whereas negative values indicate a decrease in the amount of USD, and the ESV change is presented in percent (Kindu et al, 2016;Ongsomwang et al, 2019). Finally, sensitivity analyses were performed to calculate the percentage change in ESV for a given percentage shift in the value coefficient.…”
Section: Ecosystem Service Evaluationmentioning
confidence: 99%